A CLINICAL AND ECONOMICAL ANALYSIS OF THE RESULTS PRODUCED BY THE PROGRAM OF RSV-INFECTION PROPHYLAXIS DURING THE EPIDEMIOLOGICAL SEASON OF 2012/2013 IN MOSCOW - V. I. Ignat'eva; D. U. Ovsannikov; M. V. Avksentyeva; O. U. Rebrova; K. V. Gerasimova; I. G. Soldatova; G. A. Asmolova; L. L. Pankratyeva; E. A. Degtareva (Union of pediatricians of Russia, 2013)
Introduction. Respiratory syncytial virus (RSV) is one of the main causes of lower respiratory tract infections (LRTI) in infancy. In certain categories of children the risk of development of potentially lethal severe forms of the disease requiring hospitalization, treatment within resuscitation departments and use of artificial pulmonary ventilation is significantly higher than in any other category. Palivizumab is used to prevent RSV infection in such children; its high efficacy and tolerance were proved by numerous clinical trials. The aim of this study is to assess use of palivizumab for preventing the RSV-associated LRTI in children from the groups of high risk of severe course of this pathology from a clinical economic point of view in the course of a regular stage of RSV infection immune prevention program realized in Moscow in the season of 2012/2013. Materials and methods. The study involved detailed analysis of results of LRTI immune prevention with palivizumab in a sample of 189 case report forms containing information on the children who had received 3-5 injections of the drug. The estimated number of hospitalizations and deaths in this group of children in the absence of immune prevention was calculated in the model on the basis of results of the previously conducted studies of the RSV-associated LRTI course. The authors also calculated expenses on this group of children in the presence and absence of palivizumab immune prevention, expenses per 1 disability-adjusted life year and averted economic damage due to infantile mortality increase. Results. Use of palivizumab in the group under study has possibly prevented 39 hospitalizations, including 13 hospitalizations with medical care rendering at resuscitation and intensive care units, and 1 death. Immune prevention expenses in the group under study equaled to 33,518,514.60 rubles, whereas the estimated expenses in the absence of immune prevention equaled to 1,698,103.90 rubles. Cost effectiveness increment equaled to 461,165.37 rubles per 1 disability-adjusted life year, which is only slightly more than gross domestic product (GDP) per capita in the RF in 2012 (437,476.22 rubles) and significantly lower than the triple GDP per capita (1.3 mn rubles) - the cost-effectiveness threshold recommended by the World Health Organization for application of health preservation technologies. The averted economic damage per preserved life of 1 child equaled to 29,760,927.36 rubles. Conclusion. Use of palivizumab for preventing the RSV-associated LRTI ought to be considered clinically and economically sound.